Acute myeloid leukemia induction by amphotropic murine retrovirus (4070A): clonal integrations involve c-myb in some but not all leukemias. - Wolff, L (1991)
Amphotropic murine retrovirus 4070A was demonstrated to be highly leukemogenic when inoculated intravenously into adult DBA/2 mice that were undergoing an intense chronic inflammatory response, but was nonleukemogenic in the absence of inflammation. The virus-induced promoonocytic leukemias, designated AMPH-ML, are similar morphologically and in cell surface marker expression to monocytic leukemias, called MML and MF-ML, previously shown to be induced by Moloney murine leukemia virus and MF-3 virus (a recombinant between Friend murine leukemia virus and Moloney murine leukemia virus) and resemble certain mature acute monocytic leukemias in humans (AML subtype M5). Approximately two-thirds of the AMPH-MLs (subgroup I) were demonstrated to have alterations in the 5' end of the c-myb locus, an event which occurs in 100% of MML and MF-ML. Data indicate that proviral insertions in AMPH-ML subgroup I resulted in aberrant c-myb mRNA expression and truncation of its translation product at the amino terminus. Approximately one-third of the AMPH-MLs (subgroup II) had not undergone any DNA rearrangements at the c-myb locus. In addition, their transcripts and protein products were of normal size. These latter leukemias also had not undergone DNA rearrangements in c-myc, although retroviruses expressing myc have previously been shown to induce monocyte-macrophage tumors in mice undergoing a chronic inflammation. That subgroup II leukemias had at least one clonal viral insertion suggests that there may be other sites in the cellular genome that can be activated by insertional mutagenesis in these murine acute monocytic leukemias.